2022
DOI: 10.31557/apjcp.2022.23.5.1539
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of EYA3 Protein in Ewing Sarcoma

Abstract: Objective: Among sarcomas, Ewing sarcoma (EWS) is characterized as a highly malignant type of bone tumor caused by the fusion of EWS RNA Binding Protein-1 (EWSR1)/ Friend leukemia integration 1 (FLI1) genes. The product of fusion gene gives rise to EWSR1/FLI1 which activates the activity of Eyes absent homolog 3 (EYA3) which causes tumor growth and angiogenesis. EYA3 is now considered as a therapeutic drug target for EWS . The study was designed to gather potential inhibitors for the EYA3 target using medicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…In total, 25% of patients presented with initial metastasis. They concluded that Iranian patients generally present with large tumors and advanced stage of disease, which results in short survival (5). These data, although old, urge the need for developing national guidelines for earlier diagnosis and better management of sarcoma patients, thereby improving the patient's survival and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 25% of patients presented with initial metastasis. They concluded that Iranian patients generally present with large tumors and advanced stage of disease, which results in short survival (5). These data, although old, urge the need for developing national guidelines for earlier diagnosis and better management of sarcoma patients, thereby improving the patient's survival and quality of life.…”
Section: Introductionmentioning
confidence: 99%